2020
DOI: 10.1590/fst.29819
|View full text |Cite
|
Sign up to set email alerts
|

Influence of block freeze concentration and evaporation on physicochemical properties, bioactive compounds and antioxidant activity in blueberry juice

Abstract: This study investigated the impacts of centrifugal block freeze concentration (CBFC) and evaporation processes on physicochemical properties, bioactive compounds and antioxidant activity applied to fresh blueberry juice. After three concentration cycles, the solutes were approximately 3.6 times to the initial condition (12 °Brix) and the final color (ΔE*>4.7) was darker than the fresh juice. In all cycles, CBFC obtained higher bioactive compound concentration than evaporation, with values, in the last cycle, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 32 publications
7
33
0
Order By: Relevance
“…This contrary performance has been linked to the TSS and their values cycle by cycle, i.e., as TSS increased, an increase in the organic acid content was generated, affecting the pH and TA values [ 37 ]. Besides, the results are in accordance with those obtained in CC applied to pineapple juice [ 16 ], apple juice [ 17 ] and blueberry juice [ 38 ], in which all the cryoconcentrated juices had antagonistic values in pH and TA with the increase in solutes as the cycles passed.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This contrary performance has been linked to the TSS and their values cycle by cycle, i.e., as TSS increased, an increase in the organic acid content was generated, affecting the pH and TA values [ 37 ]. Besides, the results are in accordance with those obtained in CC applied to pineapple juice [ 16 ], apple juice [ 17 ] and blueberry juice [ 38 ], in which all the cryoconcentrated juices had antagonistic values in pH and TA with the increase in solutes as the cycles passed.…”
Section: Resultssupporting
confidence: 87%
“…The values (r) between 0.9 to 1.0, indicating the direct and proportional results between TBC and TAA, i.e., each component increased or decreased, as the cycles or the days under storage progressed, respectively. A similar trend was distinguished by Casas–Forero et al [ 38 ] and Correa et al [ 57 ], who reported a high correlation (0.9 to 1.0) between antioxidant activity and bioactive compound in CC applied to blueberry juice and aqueous coffee extract, respectively.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, our values indicate that the human eye can perceive visual differences between the original sample and each cryoconcentrated sample, since all the ∆E* values were higher than 13 CIELab units. All the data and visual color had similar trend to the results reported in various studies on FC applied to fresh juices [ 27 , 31 , 43 ].…”
Section: Resultssupporting
confidence: 84%
“…Additionally, the TPCC retention represents the TPCC retained from the fresh juice in the cryoconcentrated solution. The TPCC retention was determined by Equation (2) [ 31 ]. where C o is the initial TSS; C c is the TSS at each cycle in the cryoconcentrated fraction; TPCC c is the value of TPC, TAC, and TFC at each cycle; and TPCC o is the initial value of TPC, TAC, and TFC.…”
Section: Methodsmentioning
confidence: 99%